A lived hermetic of people and place: Phenomenology and space syntax - Seamon, David (My University, 2009)
This paper examines ways in which a phenomenological approach might contribute to space syntax research, drawing on three themes that mark the heart of phenomenological investigation: (1) understanding grounded in real-world experience; (2) human immersion in world; and (3) describing the lifeworld—a person or group’s everyday world of taken-for-grantedness of which the person or group is typically unaware. A major phenomenological question is how space syntax concepts, particularly the spatial configuration of the “deformed grid,” point toward a particular kind of place structure in which the spatial-temporal regularity of individual participants potentially coalesces into a larger environmental dynamic—what is termed “place ballet”—that both sustains and is sustained by an attachment to and a sense of place.
Keywords: Body; Body-subject; Deformed grid; Phenomenology; Place; Space syntax; Place ballet